The Army of the West and civilians: Mexican-American War military government in the southwest - Penner, Damon Clark (Kansas State University, 2023)
Military history is filled with tales of battlefield glory and sacrifice. Occasionally, however, military historians find stories of peace during times of war. One of those instances in the history the U.S. Army is that of Brig. Gen. Stephen Kearny’s Army of the West in the American Southwest in the years 1846-1847. In 1846, the Army of the West was dispatched to the northern provinces of Mexico called New Mexico and Alta California to establish military governments in preparation for the planned postwar administration of them as U.S. territories. Facing unprecedented logistical challenges in their march from Fort Leavenworth to the Pacific Coast, the Army of the West achieved the aims of the War Department. The basis for this success was the rapport that some members of the army and Kearny himself built with Nuevomexicanos, Californios, and Indigenous populations to compensate for oversights in the logistical planning of Kearny’s campaign. The tolerance Kearny ordered his men to display towards the various local groups whom Kearny’s soldiers encountered helped to make up for the flawed logistical support of Army of the West’s enterprise. The ways in which Kearny and some in the army went about relating to civilians helped to cultivate respect and support for the invaders. Along with being able to obtain provisions from civilian populations to compensate for logistical shortcomings, Kearny’s men in some circumstances went against contemporary views of race, gender, and religion when trying to “stay on the good side” of the non-combatants with whom they interacted. Kearny’s campaign from Fort Leavenworth to San Diego in Alta California thus provides a unique episode little discussed in studies of the Mexican-American War, showing soldiers seeking to peacefully influence noncombatants into supporting military actions occurring around them.
Keywords: Mexican-American War; Stephen Kearny; Army of the West; Civilians; California; New Mexico